Real earnings management in public vs private firms in the GCC countries: a risk perspective. Issue 2 (8th May 2017) - Al-Amri, Khalid; Al Shidi, Saif; Al Busaidi, Munther; Akguc, Serkan
Abstract : Purpose: The purpose of this paper is to examine the use of real earnings management by private and public firms in a unique institutional setting, which is the Gulf Cooperation Council (GCC) countries. The paper also compares the level of real earnings management between public and private firms in the GCC area. Design/methodology/approach: The GCC area is a unique setting to investigate the use of real earnings management because of the low enforcement of reporting standards and supervisory rules, lack of sophisticated financial analysis, specialized media tools and high concentration of capital ownership. The authors use different models of real earnings management proposed by Roychowdhury, 2006, cash flow management, productions cost management and discretionary expenses management to examine the use of real earnings management. Findings: The paper documents evidence consistent with private and public firms using real earnings management to influence their earnings figures. The paper also shows that the level of real earnings management is higher for private firms compared to public firms when cash flow management and discretionary expenses management models are used. The production cost model results show evidence consistent with public firms only engaging in real earnings management through production cost reduction. Research limitations/implications: The results of this study might not be applicable to other emerging markets. Practical implications: The findings of this study should promote a general understanding of firms' behavior in unique environment such as GCC countries. Regulators in the GCC region should be aware that real earnings management techniques have been used by firms and that extra caution is required when auditing or analyzing the financial information of private and public firms in the GCC market. Originality/value: This paper contributes to the literature in many aspects. First, it provides additional evidence on the use of earnings management in unique market contexts outside the USA and Europe. The GCC markets share many common characteristics that make them interesting settings to be investigated. Second, this paper adds more evidence on the use of earnings management between public and private firms. In this regard, the paper adds additional evidence in the discussions proposed by Ball and Shivakumar (2005) and Givoly et al. (2010) who use two competing perspectives to investigate earnings quality in public and private firms: the demand hypothesis and the opportunistic behavior hypothesis.